PENGARUH KREDIT MODAL USAHA TANI, BIAYA PRODUKSI, DAN LUAS LAHAN TERHADAP TINGKAT PENDAPATAN USAHA TANI(STUDI PETANI SAYUR KOPERASI BERKAH TANI MAKMUR KECAMATAN PAAL MERAH) - Elsa Dwi Lestari; Siti Hodijah; Yohanes Vyn Amzar (PT. Hasba Edukasi Mandiri, 2026)
The agricultural sector plays an important role in Indonesia’s economy; however, small-scale farmers continue to face major challenges such as limited capital, high production costs, and small landholdings, which result in relatively low farm income. This study aims to analyze the socioeconomic characteristics of farmers and examine the effects of agricultural working capital loans, production costs, and land area on vegetable farming income among members of the Berkah Tani Makmur Cooperative in Paal Merah Subdistrict, Jambi City. The research applies a quantitative approach using survey data and multiple regression analysis. The findings show that most farmers are in their productive age group but have relatively low levels of education, influencing their reliance on cooperatives as a primary source of capital. Simultaneously, agricultural working capital loans, production costs, and land area significantly affect farm income. Partially, working capital loans and land area have a positive effect, while production costs have a negative effect on agricultural income.